Economic performance and unemployment: evidence from an emerging economy - Turkey - Hakan Berument; Nukhet Dogan; Aysit Tansel (Institute for the Study of Labor (IZA), 2005)
This article examines whether various macroeconomic policy shocks have different effects on overall unemployment rate and the unemployment rate by different levels of education in Turkey. These effects are assessed for total, male and female unemployment rates separately. To examine the relationship, a quarterly VAR model with a recursive order is employed to estimate the effects of real GDP, price, exchange rate, interbank interest rate, money supply and unemployment for the period from 1988:01 to 2003:04. Main findings indicate that a positive income shock reduces total unemployment while positive exchange rate and interbank interest rate innovations both increase the unemployment rate during the initial periods. The responses of high school educated unemployment rate to five macroeconomic variable shocks are different than the response of other educational unemployment rates. Furthermore, the overall results across gender are similar.
Keywords: E24; C32; 330; unemployment; economic performance; vector autoregressive regression